Mandatory human rights due diligence: What does it mean for foreign investors and why should it be in IIAs? - Yulia Levashova (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The EU's Corporate Sustainability Due Diligence Directive (CSDD) will have a significant impact on foreign investments. The CSDD will compel some non-EU companies to conduct HRDD throughout their supply chains. This Perspective emphasizes the need to align IIAs with mandatory HRDD requirements to prevent disputes and promote responsible business conduct.
Keywords: 330